The effects of leadership styles on employee performance: A case of a selected commercial bank in Botswana - Makambe, Ushe; Moeng, Gaone Joy Motlatsi (goodwood publishing, 2019)
Purpose: Leadership is essential for providing direction and motivation to employees to achieve optimal performance. Therefore, organizations must emphasize appropriate leadership styles to enhance employee performance. Based on the collaborative leadership model, this study examines the relationship between leadership styles and employee performance at a selected bank in Botswana, focusing on transactional, transformational, and participative leadership styles. Research Methodology: This study adopted a positivist paradigm with a survey research design and a quantitative approach using self-administered questionnaires. The population comprised 433 employees, of whom 200 were randomly selected as samples. Data were analyzed using SPSS, applying factor analysis, regression analysis, and one-way Analysis of Variance (ANOVA). Results: The findings indicate that participative, transformational, and transactional leadership styles are widely practiced. However, participative and transactional leadership styles have a positive and significant effect on employee performance, whereas transformational leadership has no significant impact. Conclusions: Leadership style significantly influences employee performance. Participative and transactional leadership styles enhance performance, whereas transformational leadership is less effective in this context. Organizations should prioritize engaging and structured leadership approaches. Limitations: This study used only quantitative data from employees for analysis and did not include bank leaders’ opinions. Contributions: This study contributes to the literature on leadership and employee performance in the banking sector, highlighting the effectiveness of certain leadership styles while identifying the limitations of others in improving performance.